Nocardiosis: A two-center analysis of clinical characteristics - Wang, Lumin; Xu, Yijiao; Chen, Zhisheng; Jiang, Weiwen; Xiao, Xiong; Shen, Yun; Ye, Yanrong (Frontiers in Medicine, 2022)
Objective: The objective of our study was to describe and analyse the clinical characteristics of nocardiosis. Materials and methods: We described and analysed the clinical characteristics of nocardiosis cases from two centres over the past 5 years from the following aspects: age and sex, Nocardia species, sites of Nocardia infection, test specimens, detection methods, concurrent pathogens, symptoms, imaging features, coconditions, drug susceptibility tests, antibiotic therapy/duration, outcomes and follow-up. Results: The median age of the 19 cases was 64 years, with an interquartile range (IQR) of 56–68 years. Eight cases (42.1%) were immunocompromised (corticosteroid use (62.5%), used immunosuppressants (50.0%), or had chronic nephrosis (37.5%) or diabetes mellitus (25.0%)). The comorbidities of these cases included diabetes (10.5%), chronic kidney disease (15.8%), chronic lung disease (36.8%) and rheumatic diseases (10.5%). Cough and expectoration (73.7%) was the most common symptom of nocardiosis. The respiratory tract (89.5%) was the most common site of clinical disease. Nearly half (9 cases, 47.3%) of these patients had concurrent infections. The most common Nocardia isolation site was the respiratory tract (73.7%). All patients were treated with antibiotic therapies, 63.6% patients were under two concurrent antimicrobial agents, 15.8% patients were under monotherapy, and 21.1% patients were treated with three or more concurrent antimicrobial agents. Conclusions: The uncommon life-threatening infection, Nocardiosis affects patients with structural lung disease or immunosuppression. Although capable of producing serious and metastatic disease early recognition and prompt treatment usually result in successful outcomes.